Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.7759/cureus.3179
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Chikungunya Fever Among Medical Students of Jinnah Sindh Medical University, Karachi, Pakistan

Abstract: ObjectiveChikungunya is a viral disease characterized by severe arthralgia, fever, rash, muscle pain, and neurological symptoms. Warm and humid weather, poor sanitary conditions, and improper water storage and disposal can lead to an uncontrolled outbreak of the Chikungunya virus in South Asia. Because a vaccine against the Chikungunya virus has not yet been developed, we must rely on appropriate awareness and suitable preventive measures to prevent its spread. A review of the literature shows that knowledge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The comparison of the age and education is shown in Figure 2. Out of 306 undergraduate students, 97% (297) were between 18 and 25 years of age and 3% (9) were between 26 and 44 years. Similarly, 99% (248) of graduate respondents were aged between 26 and 44 years and less than 1% (2) were between 45 and 60 years of age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison of the age and education is shown in Figure 2. Out of 306 undergraduate students, 97% (297) were between 18 and 25 years of age and 3% (9) were between 26 and 44 years. Similarly, 99% (248) of graduate respondents were aged between 26 and 44 years and less than 1% (2) were between 45 and 60 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…Insufficient emphasis on public health education deprives students of a broad outlook on healthcare systems. 9 Studies suggest that instead of improving, perceptions of medical students about the importance of preventive strategies diminish during their undergraduate years. 10,11 In the current health crisis, transmission control mainly relies on human behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The variations in the rate of responses to various questions used for scoring knowledge were also observed by previous studies. 19,22 After assessment of knowledge scores of 39 participants who were aware of chikungunya in the present study, the mean cumulative knowledge score was found to be 6.41 ±2.90 (range: 0 -10) out of 12. Regarding the level of their knowledge about chikungunya, only 30.77% (12) had good knowledge whereas 28.21% (11) had fair knowledge and 41.03% ( 16), poor knowledge.…”
Section: Discussionmentioning
confidence: 60%
“…The virus was first identified in Africa during an outbreak of a febrile illness [1]. Since then, it has spread to over 40 countries, causing significant health concerns due to its ability to cause acute and chronic musculoskeletal pain, particularly in vulnerable populations during outbreaks [2]. The virus caused urban outbreaks in Thailand in 1967 and India in the 1970s [3].…”
Section: Introductionmentioning
confidence: 99%